APLIKASI CENTRIFUGE TURNTABLE BERBASIS MIKROKONTROLER AT89C51 DENGAN PENAMPIL LCD GM2004 - Hani, Slamet (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2009)
A Centrifuge is one very important medical apparatus for separating some me-dical subtracts such as blood, urine, drugs for producing vaccines and antitoxins. Ba-sically this apparatus is centrifugal turntable equipped with a study turning mechanism and a set of tube holders to accommodate 4 up to 20 subtract sample tubes. The needed rotation controlling system was designed and constructed in steps. First, for the entire mechanical as well as electronic subsystem. Second, on the details of the electronic hardware and the connected mechanism. Third, the software needed to run the electronic hardware. Fourth, to load the controlling program into the AT89C51 microcontroller and finally the run test of the entire system. The result shows that this centrifuge regulator works sufficiently well to replace the original failing system.